The Relationship between Emotional Intelligence and Learning Discipline of Elementary School Students during the Covid-19 Pandemic - Saraswati; Prasetyo, Teguh; Wiworo Retnadi Rias Hayu (EDUPEDIA Publisher, 2022)
Successful learning is when students change personally and interpersonally by being disciplined, managing emotions, and caring about others. Discipline in learning is a process in which some rules can shape student behavior. However, based on findings in the field, some students lack discipline in assignments, lack communication, speak harshly, and cannot manage their emotions. This study aims to determine the relationship between emotional intelligence and the learning discipline of class VI elementary school students in Kampung Bulak during the Covid-19 pandemic. This research design uses a quantitative approach with correlation analysis. The number of respondents used to be the sample was 85 students with data collection techniques using emotional intelligence and learning discipline questionnaires. The results of this study are that the value of r count is 0.576 compared to the r table obtained from 85-2 = 83 = 0.2133 then, r count > r table or 0.576 > 0.2133, where the results show that there is a positive relationship regarding intelligence emotional with student learning discipline. With a significant relationship at R square 0.331 or if it is represented equal to 33.1%, the relationship between the two variables is 33.1%. The remaining 66.9% is related to other variables. The study showed a positive relationship between emotional intelligence and learning discipline in class VI students at elementary school students in Kampung Bulak during the Covid-19 pandemic.